2006
DOI: 10.1111/j.1751-0813.2006.tb12798.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of producer conducted antemortem inspection of market pigs in Australia

Abstract: With training, producer sensitivity in antemortem inspection may be high and more proficient than abattoir antemortem inspection. Use of producer inspections may have benefits for animal welfare and chain efficiency, but not food safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Even though it would be too onerous to collect such data in this way under practical conditions, Precision Livestock Farming tools could be employed [ 30 ]. Furthermore, although it is possible to collect information on animal-based welfare outcomes at slaughter during MI, several studies expressed concerns regarding its feasibility both due to time constraints and overcrowding [ 26 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though it would be too onerous to collect such data in this way under practical conditions, Precision Livestock Farming tools could be employed [ 30 ]. Furthermore, although it is possible to collect information on animal-based welfare outcomes at slaughter during MI, several studies expressed concerns regarding its feasibility both due to time constraints and overcrowding [ 26 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of detection was almost invariably greater when inspection was conducted as animals are moved past an inspector ('in-movement' inspection) versus inspection whilst animals are stationary ('pen-side' inspection), with detection probability of infectious and suspect cases during 'pen-side' inspection being as low as 30 %. Jackowiak et al (2006) also highlight concerns about detection probability during routine ante-mortem inspection, based on results following a comparison of on-farm versus abattoir ante-mortem inspection (see below). In a study to assess pen-level prevalence of clinical signs in finishing pigs, Petersen et al (2004) found that agreement between trained observers was variable, being higher for tail biting and umbilical hernias, but only fair to moderate when identifying pens holding one or more lame pigs.…”
Section: 323mentioning
confidence: 99%
“…There is an increased probability that the animals will show post-mortem abnormalities, if abnormalities were previously identified on-farm. In a later Australian study, Jackowiak et al (2006) evaluated the efficacy of on-farm ante-mortem inspection (detection of high-risk animals, impact on food safety and potential for improvement of animal welfare). The results supported the earlier work by Harbers et al (1992c), indicating that onfarm inspection may be more effective than abattoir-based ante-mortem inspection in identifying some categories of suspect pigs, particularly those with pre-existing locomotor problems that were susceptible to transport injury.…”
Section: 323mentioning
confidence: 99%
“…Gade et al (2007) emphasised that total pre-slaughter mortality was reduced eight-fold in Danish slaughter pigs during the period of halothane gene removal from the pig population. Jackowiak et al (2006) evaluated the effectiveness of on-farm antemortem inspection in Australian pig farms. From their field study it was concluded that producer inspections may have benefits for animal welfare and chain efficiency.…”
Section: Fitness For Transportmentioning
confidence: 99%